Inhalable and respirable dust from coal-fired power plant - Mohd. Din, Shamzani Affendy; Othman, Rashidi; Nik Yahya, Nik Nurul Hidayah; Hanapi, Norsyamimi (Universiti Teknologi Malaysia, 2015)
Among the anthropogenic air pollutant that lead to the global warming, this research focuses on the inhalable dust and respirable dust that comes from the emissions of coal. Recently, the demand of electricity supply in Malaysiais raising and leads to the diversification of its resources towards the non-renewable energy. Coal-fired power plant emission had been recognized as one of the manmade sources of particulate matter. 8-hours personal particulate matter sampling had been done at a coal-fired power plant with 7-hole sampler at 2 L/min air flow and cyclone sampler at 2.2 L/min air flow. This study found that 96.78 % of the result from total inhalable dust exceeds the PM10DOE Malaysia standard of 0.15mg/m3. The percentage ratio of respirable towards total inhalable dust is 50.25%. Further analysis showed that as the temperature increases, the particulate matter concentration also increases. It is believed that the smaller particles offer higher degree of human health risk. The particulate from coal with aerodynamic diameter of 2.5 micron and lesser can be deposited into deeper part of lung and provide adverse health impact towards the public or residence of surrounding coal-fired power plant location area, generally and coal-fired power plant workers, in specific.